Preparation & Characterization of Complexes Containing Beta Lactam & Study of the Effect of Corrosion Inhibition Using Iron Resistant Stainless Steel - Haneen R. Ali, Sahar S. Hassan, Nafeesa J. Kadhim (Pakistan Journal of Medical & Health Sciences, 2022)
Metal (II) complexes of Co, Ni, Cu and Zn with Amoxicillin derivative (L) were synthesized and identified by elemental analysis CHNS Uv-Vis, FTIR, TGA, metal analysis AA, magnetic susceptibility and conduct metric measurement. by analysis the ligand behaves as a bidentate. All complexes that have nickel, copper , cobalt and zinc ions were proposed as octahedral geometry shape. Protection study of the corrosion behavior of carbon steel surface was conducted with several of the zinc derivative concentrations. Experimentally, the inhibition efficiencies (%IE) in the saline solution 3.5% NaCl was examined using measurements of potentiometric polarization. The outcomes revealed that the %IE of carbon steel corrosion by amoxicillin Derivatives was 72.87%. Keywords: corrosion resistance, elemental analysis CHNS , Uv-Vis and FTIR spectroscopies, Amoxicillin derivative